Sensitivity of the diagnostic radiological index of protection to procedural factors in fluoroscopy. Issue 7 (13th June 2016) - Jones, A. Kyle; Pasciak, Alexander S.; Wagner, Louis K.
Abstract : Purpose: To evaluate the sensitivity of the diagnostic radiological index of protection (DRIP), used to quantify the protective value of radioprotective garments, to procedural factors in fluoroscopy in an effort to determine an appropriate set of scatter‐mimicking primary beams to be used in measuring the DRIP. Methods: Monte Carlo simulations were performed to determine the shape of the scattered x‐ray spectra incident on the operator in different clinical fluoroscopy scenarios, including interventional radiology and interventional cardiology (IC). Two clinical simulations studied the sensitivity of the scattered spectrum to gantry angle and patient size, while technical factors were varied according to measured automatic dose rate control (ADRC) data. Factorial simulations studied the sensitivity of the scattered spectrum to gantry angle, field of view, patient size, and beam quality for constant technical factors. Average energy ( E avg ) was the figure of merit used to condense fluence in each energy bin to a single numerical index. Results: Beam quality had the strongest influence on the scattered spectrum in fluoroscopy. Many procedural factors affect the scattered spectrum indirectly through their effect on primary beam quality through ADRC, e.g., gantry angle and patient size. Lateral C‐arm rotation, common in IC, increased the energy of the scattered spectrum, regardless of the direction of rotation. The effect of patient size on scattered radiation depended on ADRC characteristics, patient size, and procedure type. Conclusions: The scattered spectrum striking the operator in fluoroscopy is most strongly influenced by primary beam quality, particularly kV. Use cases for protective garments should be classified by typical procedural primary beam qualities, which are governed by the ADRC according to the impacts of patient size, anatomical location, and gantry angle.